The leading example of western-influenced structures in Ottoman architecture - Cit Kasr? at the Y?ld?z Palace and its repairs - Erdem, Ayten; Ilhan, Nevzat (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
cit Kasri which is one of the important buildings in the Yildiz Palace was constructed in the mid-19th century. It was probably designed and built by Sarkis Balyan, during the reign of Sultan Abdulaziz. The building is known as the cit Kasri because of the cloth material called chit that covered the interior walls. The ambassadors and officials of foreign states were received in this building. The Kasir is a single-story building of masonry construction with a partial basement. It was built generally of imported materials. In Ottoman architecture; cement materials, prefabricated imitation stone elements, and interior space decoration covered with silk cloth were certainly used for the first time in this building. The building was repaired in 1982-1983 by the Research Centre for Islamic History, Art and Culture. It was vacated in 2017 as part of the project to reunify the Yildiz Palace. Today, the building, which is currently idle, is waiting to be repaired and reused. This study's aim is to reveal the original values of cit Kasri which is in a new restoration process, to evaluate the last restoration, to share the information obtained from this restoration and the current conservation problems of the building with the academic community, and to provide data for the new restoration planned in the future. The research is based on the survey drawings of the building before the restoration, the information obtained from the building during the repair, and the photographs taken before and after the restoration.
Keywords: Cement; cloth-covered; imitation stone; ?it Kasri; westernization; Architecture